Measurement properties of a patient-reported outcome measure assessing psoriasis severity: The psoriasis symptoms and signs diary. (3rd July 2016) - Mathias, Susan D.; Feldman, Steven R.; Crosby, Ross D.; Colwell, Hilary H.; McQuarrie, Kelly; Han, Chenglong
Abstract: Background : Collecting reliable and valid symptom information from patients is critical for assessing psoriasis severity in clinical research. Objective : To evaluate measurement properties of a new patient-reported outcome (PRO), the Psoriasis Symptoms and Signs Diary (PSSD). Methods : One hundred six US patients with moderate-to-severe plaque psoriasis completed two versions of the PSSD [a 24-hour recall (PSSD-24h) and 7-day recall (PSSD-7d)] using a 0–10 numerical rating scale. Reliability (test-retest and internal consistency), validity (convergent, divergent and known-groups), responsiveness, and version equivalence were evaluated. Minimally important difference was estimated. Results : Based on exploratory factor analysis and clinical input, symptom, sign, and total severity scores were established. Internal consistency (Cronbach's alpha ≥ 0.944) and test-retest reliability (intraclass correlation coefficients ≥ 0.824) were acceptable. Correlations with Dermatology Life Quality Index (DLQI) (0.489 to 0.644) indicated convergent validity, while low correlations (< 0.30) with several Short Form (SF)-36 scales indicated divergent validity. PSSD scores differed when patients were categorized by Body Surface Area, DLQI, and Psoriasis Area Severity Index scores. PSSD-24h and PSSD-7d versions were equivalent (Pearson correlations ≥ 0.953). Limitations : PSSD responsiveness should be evaluated in patients receiving treatment. Conclusion : The PSSD is reliable and valid in measuring symptoms/signs of patients with moderate-to-severe plaque psoriasis.